An optimal investment, consumption-leisure and voluntary retirement choice problem with subsistence consumption constraints - Lee, Ho-Seok; Shin, Yong Hyun (Japan journal of industrial and applied mathematics, 2016)
We study an optimal investment, consumption-leisure and voluntary retirement problem for an agent whose consumption rate process is subject to a subsistence constraint before retirement. We use the dynamic programming method to obtain closed-form solutions for the optimal strategies as well as the value function when the agent’s utility of consumption and leisure is of Cobb–Douglas form.